Optimizing Digital Marketing for MSMEs: The Case of Tape Bakar in Melis Village, Trenggalek - Luthfi Abdul Manaf; Sergio Adorno (LP2M Universitas Islam Negeri Sayyid Ali Rahmatullah Tulungagung, 2025)
Purpose: This service program aims to increase the understanding and skills of Ms. Khasanah’s Tape Bakar business in Melis Village by optimizing the use of digital marketing. Method: The program applies the Asset-Based Community Development (ABCD) approach through training sessions, mentoring, and hands-on practice in creating promotional content and managing social media platforms. A pre-test and post-test evaluation were conducted to measure knowledge gain. Practical Applications: The application of digital marketing is expected to expand market reach, increase sales of Tape Bakar, and support family economic sustainability by combining traditional products with innovative promotional strategies. Conclusion: The results show measurable improvements: participants’ knowledge scores increased from an average of 52% (pre-test) to 84% (post-test), while Instagram followers of the business account rose from 125 to 310 within one month after training. Online engagement also improved, with product inquiries via WhatsApp Business increasing by 45%. These outcomes demonstrate that optimizing digital marketing not only strengthens product exposure but also contributes positively to the family economy through the synergy of tradition and innovation.